2022
DOI: 10.3390/land11010130
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Urban Expansion on the Loss and Fragmentation of Cropland in the Major Grain Production Areas of China

Abstract: The continuous expansion of urban land has led to massive encroachment upon cropland. To examine the impacts of urban expansion on the loss and fragmentation of cropland in China’s nine major grain production areas (MGPAs), we used standard deviation ellipse, land use transfer matrix, land use dynamic degree, and landscape metric to explore the spatio-temporal evolutions, mutual transfer, and landscape patterns of cropland and urban land. The results show the following: (1) From 1995 to 2018, the areas of crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…The study noted the importance of the size of the city as moderating variable: the largest, the first and the second tier cities conformed to the EKC relationship, while smaller cities were characterized by a linear relationship between the variables (e.g., continuous urban land‐cropland substitution). Another study of land use patterns conducted in China (Yuan et al, 2022) likewise identified nonlinearities in land use: “short‐term increase—long‐term decrease—short‐term increase” in the areas of cropland in major grain production areas, and continuous growth of urban land. The study also confirmed urban expansion as a major reason behind cropland loss.…”
Section: Theoretical Basis and Literature Reviewmentioning
confidence: 98%
“…The study noted the importance of the size of the city as moderating variable: the largest, the first and the second tier cities conformed to the EKC relationship, while smaller cities were characterized by a linear relationship between the variables (e.g., continuous urban land‐cropland substitution). Another study of land use patterns conducted in China (Yuan et al, 2022) likewise identified nonlinearities in land use: “short‐term increase—long‐term decrease—short‐term increase” in the areas of cropland in major grain production areas, and continuous growth of urban land. The study also confirmed urban expansion as a major reason behind cropland loss.…”
Section: Theoretical Basis and Literature Reviewmentioning
confidence: 98%
“…The dynamic degree of land use can quantitatively reflect the change speed of land use quantity in the study area (Yuan et al, 2022), and the formula is as follows:…”
Section: Land Use Dynamics and Land Transfer Matrixmentioning
confidence: 99%
“…The topography of Yangzhou influenced the urban land supply suitability due to its special features, displaying a fan-shaped slope from west to east. Urban land expansion was mainly fulfilled by occupying farmland, as farmland was the main supply source of urban land [ 24 , 25 ]. Thus, in this study, slope, elevation, and farmland area were selected as indicators to evaluate the regional endowment feature.…”
Section: Framework Analyzing the Driving Factors Of Urban Land Expans...mentioning
confidence: 99%